Impact of Starch Storage Condition on Glycemic Index and Resistant Starch of Cooked Potato (Solanum tuberosum) Tubers. (8th October 2020) - Lal, Milan Kumar; Kumar, Awadhesh; Raigond, Pinky; Dutt, Som; Changan, Sushil Sudhakar; Chourasia, Kumar Nishant; Tiwari, Rahul Kumar; Kumar, Dharmendra; Sharma, Srigopal; Chakrabarti, Swarup Kumar; Singh, Brajesh
Abstract: Potato is a modified stem, which is rich in starch. Very often, potato is categorized as a high glycemic index (GI) food. Consuming high GI foods should be done with moderation to prevent insulinemic spikes, which can be a preventive measure against diabetes and related disorders. A modified, inexpensive, and precise in vitro method is developed for estimation of GI in potato tubers. Among the six varieties, Kufri Chipsona‐3 exhibits the highest GI (83.08) whereas Kufri Jyoti has the lowest value (72.87); the resistant starch (RS) content being 1.08% (low) and 2.18% (high), respectively. The study shows a significant negative correlation ( R = −0.88) between GI and RS, whereas a negative nonsignificant correlation ( R = −0.79) is found between GI and amylose content. Further, the starch storage of cooked potato tubers at 4 °C for various periods (up to 48 h) results in a significant reduction in GI and increase in RS content. This newly developed protocol for estimation of GI in potato is a simple, rapid, and precise method. This will help not only the food industry but also the breeders to select the low GI genotype for their breeding program. Abstract : A modified, inexpensive, and precise in vitro method is developed for estimation of GI in potato tubers. This improved method will help potato breeders and the food industry to select low GI varieties and food.